2014
DOI: 10.4102/phcfm.v6i1.656
|View full text |Cite
|
Sign up to set email alerts
|

Maternal complication prevention: evidence from a case-control study in southwest Nigeria

Abstract: BackgroundThe importance of strengthening maternal health services as a preventive intervention for morbidities and complications during pregnancy and delivery in developing countries cannot be over-emphasised, since use of prenatal health services improves maternal health outcomes.AimThis study investigated differences in risk factors for maternal complications in booked and unbooked pregnant women in Nigeria, and provided evidence for their prevention.SettingThe study was carried out in a postnatal ward in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It also revealed that caring for these types of patients require both enough basic equipment and human resources. This would minimise some complications [26].…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also revealed that caring for these types of patients require both enough basic equipment and human resources. This would minimise some complications [26].…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
“…A study conducted in sub-Saharan Africa on reasons of women not using antenatal care service found that the high maternal mortalities are associated with unbooked pregnant mothers [9]. These circumstances affect middle and Low…”
Section: Introduction and Background Informationmentioning
confidence: 99%